The Humanity (In and Through) of Jesus of Nazareth: An Analysis of the Thought of John Shelby Spong - Masinambow, Yornan (Institut Agama Kristen Negeri Manado, 2023)
This article explores the thoughts of a character namely John Shelby Spong with his radical idea of ​​Jesus of Nazareth. Spong highlights Jesus not from a doctrinal point of view as institutional Christianity continues to echo. The Jesus echoed here is Jesus from a human perspective, a real character who lived in a place and time in the past. His life is more about humanizing humans who bring equality. John Shelby Spong was Bishop of the Episcopal Church of Newark, New Jersey from 1976 to 2000. His radical writings and lectures have challenged Christianity for many years. There are so many thoughts about the Christian faith which of course he criticizes radically, but in this paper, the researcher focuses on Spong's interpretive thoughts about Jesus of Nazareth and his practical actions. This paper uses a qualitative approach to literature that highlights certain figures. Of course, the discussion will center on the context of Spong's thought reconstructing Jesus of Nazareth the Jew. From the results of the discussion, it can be said that Jesus in Spong's thinking is a character who revives, and humanizes humans, destroys ethnic boundaries, and Jewish exclusivity, equalizes men and women, and destroys the racial prejudices and stereotypes of his time. Those who are rejected are accepted by Jesus and see him as a complete human being. That's the Jesus of Nazareth according to Spong that Christianity must live today.